Theoretical model for autoimmune thyroiditis. I. Basic model of cell immunity - Gladkikh, D. P.; Gordienko, E. A. (Biophysical Bulletin, 2005)
Based on the state-of-the-art conception of cell immunity the basic theoretical model of this phenomenon is supposed in the form of a set of balance equations for immunocompetent cells, macrophages, antigens, and antibodies.